PENGARUH KUALITAS JASA KONSULTAN PAJAK DAN PENGETAHUAN PAJAK TERHADAP KEPATUHAN WAJIB PAJAK (STUDI PADA WAJIB PAJAK PENGGUNA JASA KANTOR KONSULTAN PAJAK DONI BUDIONO) - Fauzhi, Imam (Jurnal Mahasiswa Perpajakan, 2015)
This research is conducted based on low number of tax servants to help taxpayers in fulfilling their tax obligations. This condition gives impact to some of taxpayers in using the tax consultant service. Taxpayers expect that the tax consultants are able to help in resolving tax problems that are being undertaken by the taxpayer. Those taxpayers expectation requires the tax consultant to have a good quality services to improve taxpayer compliance. Another factor affecting tax compliance is the tax knowledge of the taxpayer. The type of research conducted in this study is an explanatory research by using quantitative approach and using questionnaires as data collection methods. The populations in this study are the whole taxpayers who use the tax consultant services. The samples involved in this study are 43 respondents. Based on the F test result, it is noted that the quality of tax consultantâ€™s service quality and tax knowledge is jointly having a significant effect on taxpayer compliance. While based on the results of t-test is noted that the quality of tax consulting service quality. And tax knowledge is a partially having Â significant effect on taxpayer compliance. Tax Knowledge has a dominant influence on tax compliance. Keywords: tax consultants service quality, tax knowledge, taxpayer compliance